Trans-pacific economic relations and US-China business cycles: Convergence within Asia versus US economic leadership - Andrew Hughes Hallett; Christian Richter (Asian Development Bank Institute (ADBI), 2011)
This paper tests the hypothesis that the links and leadership/dependency relationships between the People's Republic of China (PRC), the United States (US), and the other large Asian economies have changed over the past 20 years with the industrialization of the PRC economy. We use time-varying spectral methods to decompose the links between seven advanced Asian economies and the US. We find: (a) the links with the US have been weakening, while those within a bloc based on the PRC have strengthened; (b) that this is not new - it has been happening since the 1980s, but has been partly reversed by the recent surge in trade; (c) that there are two blocs within the Asian economic area: one based on Japan and the Republic of Korea and the other on the PRC and her satellites; (d) that product composition is responsible for this division (and for some movement between the blocs); and (e) that the links between the PRC and the US are rather complex, with the US able to shape the cycles elsewhere through her control of monetary conditions, but the PRC able to control the size of the cycles at home and (to some extent) abroad.
Keywords: C22; C29; C49; F43; O49; 330; Wirtschaftswachstum; Industrialisierung; China; Konjunkturzusammenhang; Asien; Großmacht; USA